Possessing nature museums, collecting, and scientific culture in early modern Italy - Findlen, Paula 1964- (Studies on the history of society and culture, 1994)
In Possessing Nature, Paula Findlen vividly recreates the lost world of late Renaissance and Baroque Italian museums and demonstrates its significance in the history of science and culture. Based on exhaustive research into natural histories, letters, travel journals, memoirs, and pleas for patronage, Findlen describes collections and collectors great and small, beginning with Ulisse Aldrovandi, professor of natural history at the University of Bologna. Aldrovandi, whose museum was known as the "eighth wonder" of the world, was a great popularizer of collecting among the upper classes. From the universities, Findlen traces the spread of natural history in the seventeenth century to other learned sectors of society: religious orders, scientific societies, and princely courts